Perbandingan Ekonomi Konvensional dan Ekonomi Islam - Novita Lidyana (Fakultas Ekonomi dan Bisnis Islam, 2015)
Islamic economy is an economy based on divinity. There is afundamental difference in the paradigm of Islamic economics and conventional economics. Conventional economic as sumes an economic system that provides considerable freedom to everyone to carry out economic activities but with government intervention. While the Islamic economy is based on religious principles. Islamic Economic System distinguish between the economic point of view the production of goods and services covered from the perspective of the way to get it, touse and todistribute goods and services as an inseparable unit.